Pengembangan Media Digital Concept Mapping Berbasis Inkuiri pada Mata Pelajaran IPA Materi Perbedaan Waktu dan Pengaruhnya di Kelas VI Sekolah Dasar - Lestari, Deska Ria (UNIB Press, 2024)
This research aims to create: Inquiry-Based Digital Media Concept Mapping in Science Lessons on Time Differences and Their Influence. This research is development research (Reseach and Development) with the Four D (4D) model. The research object is inquiry-based digital concept mapping media. The research stages consist of four stages, namely defining, designing, developing and disseminating. This research was only carried out until the development stage, namely validity testing and practicality testing. The instruments used were a validity test questionnaire and a practicality test questionnaire. The validity test was carried out by 6 validators, namely 2 material experts, 2 language experts and 2 graphics experts. The practicality test was carried out on 31 class VI students at SDN 25 Lubuklinggau. Data analysis uses percentage techniques and is processed descriptively. The results of the feasibility test for Inquiry-Based Digital Concept Mapping Media by the validator were reviewed in terms of aspects of the home page, table of contents, study instructions, appropriateness of the material, language presentation, and graphical appropriateness, the appropriateness of the material was obtained 0.81 (very feasible criteria), the results of the appropriateness of the language were 0.75 (feasible criteria) and graphic feasibility results 0.80 (very feasible criteria). The results of the Inquiry-Based Digital Media Concept Mapping field test obtained a score of 75.03 by teachers and 84.96 by students with positive criteria. It can be concluded that the response to the use of Inquiry-Based Digital Concept Mapping Media at SDN 25 Lubuklinggau class VI is appropriate and positive.